2021
DOI: 10.1016/j.jacbts.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Nonalcoholic Fatty Liver Disease and Heart Failure With Preserved Ejection Fraction

Abstract: Highlights There is a bidirectional relationship between HF and liver disease. NAFLD may drive some HFpEF phenotypes. This review proposes 3 HFpEF phenotypes: obstructive HFpEF, metabolic HFpEF/NAFLD, and advanced liver disease/cirrhosis HFpEF. Additional studies are required to explore the pathophysiology and hemodynamic parameters of these phenotypes and investigate potential treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 116 publications
0
50
0
2
Order By: Relevance
“…This more pathogenic form of NAFLD progresses to fibrosis in approximately 35% of patients, significantly raising the risk for development of hepatocellular carcinoma (HCC), cirrhosis, and acute liver failure. Advanced NAFLD is also a significant risk factor for development of type 2 diabetes and cardiovascular diseases (CVD) (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…This more pathogenic form of NAFLD progresses to fibrosis in approximately 35% of patients, significantly raising the risk for development of hepatocellular carcinoma (HCC), cirrhosis, and acute liver failure. Advanced NAFLD is also a significant risk factor for development of type 2 diabetes and cardiovascular diseases (CVD) (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…A heart-liver axis, that was drafted by in ammatory reactants from the heart and the liver, placed a new spotlight on the crosstalk of organs in disease development 22,44 . In the phenomapping analysis of HFpEF, one of phenogroups demonstrated high proin ammatory biomarkers including tumor necrosis factor-alpha-mediated in ammation, liver brosis, and tissue remodeling 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the correlation of elevated UA level with adverse outcomes of HFpEF [18][19][20] . Moreover, renal dysfunction 21 and liver diseases, such as nonalcoholic fatty liver disease 22 and liver stiffness 23 , were clinical co-morbidities for HFpEF. However, diagnostic scoring systems for HFpEF do not contain the in ammatory markers and markers for liver and renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some HFpEF phenotypes seem to be cardiac manifestations of NAFLD, thus supporting the novel concept of a pathophysiological continuum between NAFLD and HFpEF. Such a view is supported by multiple shared pathophysiological mechanisms that rely on increased systemic inflammation [ 67 ] and contribute to the associated endothelial dysfunction [ 67 ]. Indeed, NAFLD and nonalcoholic steatohepatitis (NASH) favor the accumulation of epicardial fat secreting proinflammatory adipocytokines, thus causing microvessel dysfunction and adjacent myocardium fibrosis.…”
Section: Key Summary Pointsmentioning
confidence: 99%